The Digital Health Horizon: Emerging Trends and the AI-Driven Transformation in 2025 - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The healthcare landscape is undergoing a profound and rapid transformation, driven by the convergence of advanced technology and a growing demand for persona...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care